Analisis Profitabilitas Pada Hotel Permai Luwuk Kabupaten Banggai: Profitability Analysis at the Permai Luwuk Hotel Banggai Regency - Puspita Dewi; Clara NM. Rotinsulu; Vira Tandiawan (Jurnal Ilmiah Produktif, 2020)
The purpose of this study was to measure the Financial Performance of Permai Luwuk Hotel Management by using profitability ratios, such as Net Profit Margin (NPM) and Return of Total Assets (ROA). This research is evaluative research conducted by analyzing the financial statements of the Permai Luwuk Hotel management and interviews to get more in-depth information. The results of this study indicate that the financial performance of the Permai Luwuk Hotel is high because it is seen from the average NPM value from 2014-2018 of 71% which is higher than the target of 40% and ROA seen from the average value from 2014-2018 of 26 % is higher than the interest rate (10% - 12% per annum). These results indicate that it is very efficient in managing assets and costs for 5 years, namely from 2014-to 2018